2022
DOI: 10.1038/s41598-022-22073-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial assessing the efficacy of Silymarin on endometrioma-related manifestations

Abstract: To study the effect of silymarin on the Interleukin-6 (IL-6) level, size of endometrioma lesion, pain, sexual function, and Quality of Life (QoL) in women diagnosed with endometriosis. This randomized, double-blind placebo-controlled clinical trial was performed on 70 women with endometriosis which was divided into two groups of intervention and control. The intervention was 140 mg silymarin (or matching placebo) administered twice daily for 12 weeks. The volume of endometrioma lesions, the level of IL-6 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Cerum oxide nanoparticles, resveratrol, vitamin E, vitamin C, and epigallocatechin-3-gallate (EGCG) were among the antioxidant agents that were frequently used. Research conducted by Amini et al and Mirzaei et al demonstrated that a combination of 1000 mg/day of vitamin C and 800 IU/day of vitamin E, or 140 mg of livergol, for a period of 12 weeks significantly alleviated pelvic pain, dysmenorrhea, and dyspareunia (p<0.05) [7,8]. Nodler et al study, on the other hand, discovered no significant impact on it [9].…”
Section: Introductionmentioning
confidence: 96%
“…Cerum oxide nanoparticles, resveratrol, vitamin E, vitamin C, and epigallocatechin-3-gallate (EGCG) were among the antioxidant agents that were frequently used. Research conducted by Amini et al and Mirzaei et al demonstrated that a combination of 1000 mg/day of vitamin C and 800 IU/day of vitamin E, or 140 mg of livergol, for a period of 12 weeks significantly alleviated pelvic pain, dysmenorrhea, and dyspareunia (p<0.05) [7,8]. Nodler et al study, on the other hand, discovered no significant impact on it [9].…”
Section: Introductionmentioning
confidence: 96%
“…In October 2022, a randomised trial was conducted to study Silymarin's efficacy on endometrioma-related manifestations. 4 The trial was the first of its kind. It showed that Silymarin, a herbal supplement with potent antioxidant effects, significantly decrease endometrioma size and the chronic pelvic pain related to it.…”
mentioning
confidence: 99%
“…It showed that Silymarin, a herbal supplement with potent antioxidant effects, significantly decrease endometrioma size and the chronic pelvic pain related to it. 4 Oxidative Stress, an imbalance between ROS and antioxidants, is known as a primary factor in the endometriosis pathogenesis 5 and Silymarin may be ten times as potent as Vitamin E, another antioxidant which has been investigated in relation to endometriosis treatment. 4 In Pakistan, the estimated prevalence of endometriosis is 16.8% 6 which means a significant number of women are living with the manifestations that come with the disease, including endometriomas, which are seen in 17 to 44% of individuals with endometriosis.…”
mentioning
confidence: 99%